Managing HIV and AIDS stigma in the workplace : case study of the Eastern Cape Department of Social Development - Mnyanda, Yoliswa Ntuku (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2006.